2007
DOI: 10.1007/s00265-007-0530-z
|View full text |Cite
|
Sign up to set email alerts
|

Friendships between males and lactating females in a free-ranging group of olive baboons (Papio hamadryas anubis): evidence from playback experiments

Abstract: International audienceClose association between an anoestrous female at the time of lactation and adult male(s) is relatively rare in mammals, but common in baboons (Papio hamadryas subsp.). The functional significance of these “friendships” remains unclear, however. In chacma baboons (P. h. griseipes), friendships are a counter-strategy to infanticide by immigrant males. Experimental playback of female distress calls in chacma baboons revealed that male friends are more motivated to protect females and infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 25 publications
3
93
0
Order By: Relevance
“…Females may use post-copulatory grooming to avoid further matings with the male: Gumert (2007) showed that female grooming of males reduces subsequent copulation frequency. Alternatively, females may profit from direct potential gains, such as male support and reduction of harassment, particularly relevant to females nursing offspring from a previous mating season (Palombit et al 1997(Palombit et al , 2001Lemasson et al 2008). Comparing nursing and non-lactating females showed that lactating females initiated grooming at similar rates after either copulation type, whilst non-lactating females initiated grooming more after non-ejaculatory copulations than after ejaculatory matings.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Females may use post-copulatory grooming to avoid further matings with the male: Gumert (2007) showed that female grooming of males reduces subsequent copulation frequency. Alternatively, females may profit from direct potential gains, such as male support and reduction of harassment, particularly relevant to females nursing offspring from a previous mating season (Palombit et al 1997(Palombit et al , 2001Lemasson et al 2008). Comparing nursing and non-lactating females showed that lactating females initiated grooming at similar rates after either copulation type, whilst non-lactating females initiated grooming more after non-ejaculatory copulations than after ejaculatory matings.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, decreased female fertility associated with lactation may be relevant to differences in post-copulatory social behaviour expressed by and directed towards lactating versus non-lactating females. Other motivational factors may also influence lactating females' post-copulatory social behaviour: Previous research suggests that females with infants may be inclined to bond with male (mating) partners as they can offer protection and social support for the females and their infants (Palombit et al 1997(Palombit et al , 2001Lemasson et al 2008) and thus potentially increase offspring survival.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of other social influences that can affect the response of a focal animal to a stimulus presented during a playback experiment include the personality and social rank of nearby group members, as well as the strength of the relationship between the focal animal and nearby conspecifics. For example, playbacks of female distress calls in chacma and olive baboons elicited a stronger response in some males than others [107,108]. Males that exhibited close affiliative bonds, or 'friendships' with females (characterized by high rates of allo-grooming and infant handling and low rates of agonism) responded more strongly (measured as visual orientation and movement toward the speaker) to playbacks of their female 'friend' in distress than did control males.…”
Section: The Use Of Playback Experiments To Assess Quantitative Abilimentioning
confidence: 99%
“…Indirectly this is associated with higher reproductive success, e.g. in female baboons [25][26][27] and humans [28], and in male macaques [29], chimpanzees [30], and baboons [31].…”
Section: Introductionmentioning
confidence: 99%